2012
DOI: 10.1186/1471-230x-12-98
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the sigmoid colon with multiple liver metastases and gastric cancer: a case report

Abstract: BackgroundLeiomyosarcoma (LMS) of the gastrointestinal tract is an extremely rare high-grade neoplasm with poor prognosis. For advanced LMS with distant metastasis, the decision as to the choice of the most appropriate therapeutic strategy, including chemotherapy and surgery, is difficult. Here, we present an unusual case of LMS of the sigmoid colon with liver metastases and gastric cancer. The survival of this patient was prolonged by a combined modality therapy involving chemotherapy and surgery.Case present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Studies have revealed that the use of imatinib for palliative chemotherapy is also effective because the two-year progression free survival (PFS) was 75% with the use of standard imatinib dose in patients with unresectable or metastatic GIST [20], [21]. In contrast, it is difficult to assess the efficacy of palliative treatments of LMS due to the paucity of published reports [22]. Doxorubicin, ifosfamide, dacarbazine, and gemcitabine are commonly used in first-line chemotherapeutic regimens, although standardized chemotherapy with currently available agents has not yet been established for LMS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that the use of imatinib for palliative chemotherapy is also effective because the two-year progression free survival (PFS) was 75% with the use of standard imatinib dose in patients with unresectable or metastatic GIST [20], [21]. In contrast, it is difficult to assess the efficacy of palliative treatments of LMS due to the paucity of published reports [22]. Doxorubicin, ifosfamide, dacarbazine, and gemcitabine are commonly used in first-line chemotherapeutic regimens, although standardized chemotherapy with currently available agents has not yet been established for LMS.…”
Section: Discussionmentioning
confidence: 99%
“…A specific molecular therapy is currently available for GIST, but not for LMS. Reports indicate that 30-60% of clinical response rates can be achieved in the treatment of LMS using combinations of docetaxel and gemcitabine [2], and in the treatment of advanced soft tissue sarcoma using ifosfamide with anthracycline and/or dacarbazine [2]. According to Hamai et al only first line chemotherapy with docetaxel and S-1 was found to be effective against both the gastric cancer and LMS.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcomas (LMS) of GIT are extremely rare mesenchymal neoplasms which account for 0.12% of colon cancers. Only a few reports have been published on GIT mesenchymal tumors [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…LMS are known to hematogenously metastasize to the lungs, liver, bones and brain. Other sites of metastasis are relatively rare [21][22][23] . Also, although other soft tissue sarcomas have been reported as metachronous, there no reports of metachronous LMS but there are few series of multicentric (synchronous).…”
Section: Discussionmentioning
confidence: 99%